Study on the Protective Effect of the KIR3DL1 Gene in Ankylosing Spondylitis. Issue 11 (November 2015) - Vendelbosch, S.; Heslinga, S. C.; John, M.; van Leeuwen, K.; Geissler, J.; de Boer, M.; Tanck, M. W. T.; van den Berg, T. K.; Crusius, J. B. A.; van der Horst‐Bruinsma, I. E.; Kuijpers, T. W.
Abstract : Objective: Ankylosing spondylitis (AS) is an autoimmune disease that mainly affects the sacroiliac joints and the spine of the lower back. The disease is strongly associated with HLA–B27. Additional genes, single‐nucleotide polymorphisms, and molecular components have been identified to be associated with AS, but the exact mechanism that drives disease development remains poorly understood. The killer cell immunoglobulin‐like receptors (KIRs) are regulators of cytotoxicity of natural killer cells and T cell subsets and may be relevant in binding to HLA–B27 and the development of AS. We undertook this study to identify possible associations of KIR genotype with susceptibility to AS and disease characteristics including the presence of the HLA–B27 allele, disease severity, and uveitis. Methods: We performed complete genotyping of the KIR locus in 303 Caucasian AS patients, 119 randomly selected healthy Caucasian controls, and 50 HLA–B27–positive healthy Caucasian controls by multiplex ligation‐dependent probe amplification assay for detection of gene presence and copy number. Results: We did not observe a significant association of any specific KIR gene or haplotype with susceptibility to AS or any other clinical manifestation. Disease severity, as measured by fulfilling the criteria for treatment with tumor necrosis factor blocking therapy, was linked to a lower number of genes for the functional variant of KIR3DL1 ( P = 0.007). Conclusion: Our exploratory study indicates that KIR genes are not a major risk factor for susceptibility to AS. However, the data do suggest a role for KIRs in progression of the disease, whereby KIR3DL1 has a protective effect against the more severe manifestations of AS.